Coexistence of familial Mediterranean fever and rheumatoid arthritis. Issue 1 (January 2014) - Migita, Kiyoshi; Abiru, Seigo; Sasaki, Osamu; Miyashita, Taiichiro; Izumi, Yasumori; Nishino, Ayako; Jiuchi, Yuka; Kawakami, Atsushi; Yasunami, Michio
Abstract: Familial Mediterranean fever (FMF) is an autoinflammatory disorder characterized by recurrent febrile polyserositis and arthritis. Although accompanying seronegative spondyloarthropathy has been reported in FMF, coexistence with rheumatoid arthritis (RA) is very rare. This case report describes a Japanese female RA patient who presented with periodic fever. Genetic analysis revealed compound heterozygous mutations in exon 2 and 3 of the MEFV gene (E148Q/G304R/P369S/R408Q). The patient was successfully treated with colchicine with 3-year follow-up.